Lembaga keuangan mikro syari'ah : pergulatan melawan kemiskinan & penetrasi ekonomi global - Muhammad, 1971- (Yogyakarta : Graha Ilmu, 2009)
On microfinance institutions from sharia perspective for alleviation of poverty in Indonesia.
Includes bibliographical references (p. [121]-125).
Keywords: Microfinance -- Religious aspects; Microfinance -- Law and legislation; Banking law (Islamic law).